Correlation between nicotine dependence and barriers to cessation between exclusive cigarette smokers and dual (water pipe) smokers among Arab Americans - El-Shahawy O; Haddad L (Dove Medical Press, 2015)
Omar El-Shahawy,1 Linda Haddad2 1Department of Social and Behavioral Health, School of Medicine, Virginia Commonwealth University, Richmond, VA, USA; 2College of Nursing, University of Florida, Gainesville, FL, USA Background: Evidence suggests that dual cigarette and water pipe use is growing among minority groups, particularly among Arab Americans. Differences in nicotine dependence and barriers to smoking cessation among such dual smokers have not been previously examined in this population. We examined potential differences that might exist between exclusive cigarette smokers and dual smokers (cigarette and water pipe) pertaining to nicotine dependence and barriers to cessation among Arab Americans. Methods: We conducted a cross-sectional study using a convenience sample of self-identified Arab immigrant smokers (n=131) living in the Richmond, VA metropolitan area. Data were collected using four questionnaires: Demographic and Cultural Information questionnaire, Tobacco Use questionnaire, Fagerström Test for Nicotine Dependence (FTND) questionnaire, and Barriers to Cessation questionnaire. We examined differences in nicotine dependence and barriers to cessation between exclusive cigarette smokers and dual smokers of cigarettes and water pipe. Furthermore, we explored the correlations of these measures with select variables. Results: There was a significant difference in the FTND scores between the exclusive cigarette smokers (mean M=2.55, standard deviation [SD] =2.10) and dual smokers (M=3.71, SD =2.42); t(129) = (2.51), P=0.0066.There was also a significant difference in the Barriers to Cessation scores between exclusive cigarette smokers (M=38.47, SD =13.07) and dual smokers (M=45.21, SD =9.27); t(129) = (2.56), P=0.0058. Furthermore, there was a highly significant correlation among FTND scores, Barriers to Cessation scores, and past quit attempts among dual smokers. Conclusion: Water pipe tobacco smoking seems to be both adding to the dependence potential of cigarette smoking and enhancing barriers to cessation in our study sample. However, the high correlation between quit attempts, FTND, and barriers to cessation needs further investigation to ascertain the possible reasons behind it. This preliminary study utilized a cross-sectional survey among participants of a rather small convenience sample, especially in the dual smokers group. Thus, there is a need to examine these differences via a longitudinal design in a larger sample. Keywords: Arab Americans, cessation barriers, dual use, nicotine dependence, water pipe smoking